RUMEN MODIFIERS: A REVIEW - POSSAMAI, A. P.S.; LALA, B.; PEREIRA, V. V.; GOMES, L. C.; SILVA, S. C.C. (Revista Brasileira de Engenharia de Biossistemas, 2011)
The digestive process of ruminants comprises one of the most successful symbiotic relationships between organisms. The rumen, main ruminants digestion organ, is considered a fermentation chamber which presents environmental conditions suitable for the development and multiplication of microorganisms unicellular. The modern practice of ruminants feedings, which increased production levels present new challenges to the rumen microflora. The aim of this review is to discuss the main substances used as modifiers of ruminal fermentation and their mechanisms of action